The Transformative Role of Artificial Intelligence in Healthcare: Innovations, Challenges, and Future Direction - Jagdale, Tejas Ajinath; Bhapkar, Yogita V; Bhegade, Neha Tukaram; Kannor, Tanuja Mangesh (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network; Vol 9 No 2 (2025): Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2025)
Artificial Intelligence (AI) is changing healthcare by making it more precise, efficient and accessible. AI’s applications including precision medicine, medical imaging, telemedicine and mental health enable personalised care and better diagnosis. Machine learning models can analyse large datasets to predict disease risks, detect anomalies in medical imaging and support early diagnosis. Predictive analytics can also detect and intervene early for chronic diseases. In workflow management AI can automate routine tasks and streamline processes. Despite the potential challenges like algorithmic bias, data privacy concerns, high implementation costs and ethical dilemmas are big barriers to adoption. Collaboration among healthcare professionals, technologists and policymakers is key to developing transparent and accountable AI systems. By addressing these challenges through legal frameworks, standardised data practices and AI integrated medical education the healthcare industry can unlock the full potential of AI and ensure equitable access, better patient outcomes and sustainable innovation.